2012
DOI: 10.1088/1367-2630/14/7/073014
|View full text |Cite
|
Sign up to set email alerts
|

Focusing of a neutral helium beam below one micron

Abstract: In 2008 we presented the first images obtained with a new type of matter wave microscope: NEutral Helium Atom MIcroscopy (NEMI). The main features in NEMI are the low energy of the atoms (<0.1 eV) and the fact that they are neutral. This means that fragile and/or insulating samples can be imaged without surface damage and charging effects. The ultimate resolution limit is given by the de Broglie wavelength (about 0.06 nm for a room-temperature beam), but reaching a small focus spot is still a major challenge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…The larger the source (skimmer) and the smaller the speed ratio, the larger this effect will be. It has previously been shown that the analytical model provides good agreement for small skimmers in the micrometer range (see, for example, [9]). The MCSTAS simulations predict only a very small change in focus size with speed ratio and fit the data very well except for the footprint to the right, which is slightly raised.…”
Section: Fig 3 Experimental Focusing Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The larger the source (skimmer) and the smaller the speed ratio, the larger this effect will be. It has previously been shown that the analytical model provides good agreement for small skimmers in the micrometer range (see, for example, [9]). The MCSTAS simulations predict only a very small change in focus size with speed ratio and fit the data very well except for the footprint to the right, which is slightly raised.…”
Section: Fig 3 Experimental Focusing Resultsmentioning
confidence: 90%
“…A simplified model for the final focused spot size is given by approximating the source image and w with Gaussian functions. The skimmer diameter d sk is taken to be the FWHM of the object function [9]. We thus obtain for the theoretical final spot size d focus ,…”
Section: A Analytical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresnel zone plates have larger apertures but still block large portions of the incident beam. [4][5][6] Zone plate focusing has recently achieved resolution on the order of 1 µm. Standing light waves, which interact with atoms via the AC Stark effect, are amenable to a variety of shaping and tuning techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The smallest free-standing features made so far for such applications are around 50 nm, 7 and even less would be desirable. 12 This calls for alternative approaches, such as UV or deep UV lithography, electron-beam (e-beam) lithography, nanoimprint lithography, or scanning probe lithography.…”
Section: Introductionmentioning
confidence: 99%